Betaine as a dietary supplement for finishing cattle - C.A. Loest; R.D. Hunter; R.H. Wessels; James S. Drouillard; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1998)
One hundred seventy five steers (902 lb initial body weight) were used in a finishing study to determine the effect of betaine, provided either as feed-grade betaine (Betafin-S6, Finnsugar Bioproducts) or as concentrated separator by-product (CSB; desugared beet molasses), on animal performance and carcass characteristics. Steers were fed a finishing diet based on steam-flaked and dry-rolled corn. Treatments included 10.5 or 21 g/steer daily supplemental feed-grade betaine or 250 g (15.5 betaine) or 500 g (31 g betaine) of CSB per steer daily. Dry matter intakes increased (linear, P<0.1) for steers supplemented with feed- grade betaine. Average daily gains and feed efficiencies were not affected by treatments. Dressing percent and twelfth rib back fat increased (P<0.1) for steers that received feed-grade betaine. Rib-eye area decreased (P<0.1) when steers were supplemented with either feed-grade betaine or CSB. Yield grades were significantly higher (linear, P<0.1) for cattle receiving supplemental CSB or feed-grade betaine (quadratic, P<.05). Hot carcass weights, KPH, marbling scores, and percentage of carcasses grading USDA Choice were not affected by supplemental betaine. In this study, betaine supplementation did not markedly alter growth performance, but carcass fatness tended to increase for both supplements.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Betaine; Steers; Performance; Feedlot carcasses